Deep brain stimulation as a treatment for neuropathic pain: a longitudinal study addressing neuropsychological outcomes. - Gray, A; Pounds-Cornish, E; Eccles, F; Aziz, T; Green, A; Scott, R (2014)
UNLABELLED: Deep brain stimulation (DBS) of the periventricular/periaqueductal gray area and sensory thalamus can reduce pain intensity in patients with neuropathic pain. However, little is known about its impact on quality of life, emotional well-being, and cognition. This study followed up 18 patients who had received DBS for neuropathic pain. Each participant had previously undergone psychometric evaluation of each of the above areas as part of a routine presurgical neuropsychological assessment. Commensurate measures were employed at a follow-up assessment at least 6 months postsurgery. DBS significantly improved mood, anxiety, and aspects of quality of life. Improvements correlated with reduced pain severity. However, the sample continued to show impairments in most areas when compared against normative data published on nonclinical samples. There was little change in general cognitive functioning, aside from deterioration in spatial working memory. However, improvements in pain severity were associated with less improvement (and even deterioration) on measures of executive cognitive functioning. Improvements in emotional well-being also were correlated with changes in cognition. These results suggest that DBS of the periventricular/periaqueductal gray and/or sensory thalamus improves quality of life and emotional well-being in sufferers, although there is some indication of executive dysfunction, particularly among those reporting greatest pain alleviation. PERSPECTIVE: This article examines the neuropsychological outcomes of DBS surgery as a treatment for neuropathic pain. This intervention was found to improve pain severity, emotional well-being, and quality of life, although such benefits may be accompanied by reduced ability on tasks measuring executive functioning.